Sleep quality and coping styles among diploma nursing students in Universiti Sains Malaysia (USM) - Syazwani, Md Zamri (Pusat Pengajian Sains Perubatan, 2011)
Students had encountered more sleep disturbances compared with the others population. Sleep quality can give an effect in daily life and play the important role in determining individual physical health, performances and psychological status. Sleep quality also can influence individual choices of coping styles. The objectives of this study are to determine the level of sleep quality among diploma nursing students in USM as well as to identify the relationship between sleep quality and coping styles. This study involved diploma nursing students in USM, Kubang Kerian. Data was collected using Sleep Quality Index and the Coping Styles Questionnaire. Descriptive statistic was used to describe the characteristics of the respondents while Chi-square test was used to tested the correlation between variables, where p-value = 0.35, which were not significant. Results found that the students had poor sleep quality and most of them used adaptive coping styles when facing the problem. There were no relationship (p > 0.05) between sleep quality and coping styles among diploma nursing students. Considering the students were having poor sleep quality, health education is an area which needs to be addressed immediately to improve student's knowledge about good sleep quality and practice to improve it.